Evaluasi Kondisi Jalan Angkut dari Front Penambangan Menuju Rom Stockpile untuk Mencapai Target Produksi 15.000 Ton Batubara Perbulan PT. Prima Dito Nusantara Jobsite KBB Kabupaten Sarolangun, Provinsi Jambi - Bram Subhan Maulana; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2018)
Coal production produced by PT. Prima Dito Nusantara by dumptruck is currently 9.977,48 ton/bulan, looking at the condition of the existing equipment, it is planned to produce daily from the dumptruck to be further improved so that the production that can be achieved by the dumpt truck can reach 15,000 tons / month. Therefore, the problem to be examined is "is the condition of the haul road being used at this time ideal to achieve the coal production target of PT .Prima Dito Nusantara". With the evaluation of haul roads are expected to help the problems that exist in the company so that the productivity of the means of transportation to increase and production to be achieved. The research method conducted in the field is by measuring along the haul road from the mining front to the rom stocpile by calculating the width of the haul road, the distance and the slope and then comparing the actual condition in the field with the result of calculation based on the theory. The results showed that the width of the minimum haul road for straight road conditions must be made that is 11 m and 15 m for the bend.The slope at the bend (superelevation) with the theoretical bend width of 15 m must be made 30 cm so that the transport can pass the bend with maximum speed. Based on the theoretical width of the cross slope to be made is 22 cm to the side of the road so that the road body is not inundated with water, while the slope of the haul road is 15%. The results of the research analysis will then be made a recommendation as a solution of the problems that occur. Keywords: Hauling Road, Cross Slope, Superelevation, Road Transport Slope, Coal Production.